Persepsi Pelaku Usaha terhadap Mekanisme Sistem Online Single Submission dalam Mempercepat Proses Perizinan di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Provinsi Jambi - Rizal Jalil; Moh. Ihsan; Fitri Widiastuti (Masip: Jurnal Manajemen Administrasi Bisnis dan Publik Terapan, 2025)
This study aims to analyze the perceptions of business actors regarding the Online Single Submission (OSS) system mechanism in accelerating the licensing process at the Investment and One-Stop Integrated Services Office of Jambi Province. The research method used is qualitative, with data collected through observation, interviews, and documentation. The results of the study indicate that the implementation of OSS is considered to facilitate and accelerate the business licensing process. Business actors appreciate the ease of access and time efficiency provided by the system. However, several challenges were still found, including limited internet network availability, low technological understanding among some business actors, and a lack of socialization regarding the use of OSS. Therefore, this study recommends the need for improved assistance for business actors, more intensive socialization, and strengthening of infrastructure, especially internet networks, to ensure the optimal implementation of OSS. Thus, it is hoped that this system can be more effective in supporting the acceleration of business licensing in Jambi Province.